Digital Transformation and Organizational Resilience: The Mediating Role of Digital Literacy - Yen Efawati; Rachman, Adryan; Andriani, Rian; Veranita, Mira; Rinawati (International Journal Administration, Business & Organization, 2025)
In an increasingly turbulent and digitalized environment, organizational resilience has become a critical capability enabling organizations to survive and thrive amid unexpected disruptions. Drawing on the digital transformation and organizational resilience framework, this study examines the role of digital literacy as a mediating mechanism through which digital transformation enhances organizational resilience. Although prior studies highlight the importance of digital transformation in strengthening resilience, limited attention has been given to the human-capability mechanisms that explain how this relationship unfolds. Addressing this gap, the present study integrates digital literacy into the digital transformation and organizational resilience. Using a quantitative research design, data were collected from 224 SME owners in the retail sector in Greater Bandung and analyzed using structural equation modeling. The results indicate that digital transformation has a positive and significant effect on digital literacy, suggesting that digitally mature organizations are more likely to foster owner digital capabilities. In addition, digital transformation is found to directly and positively influence organizational resilience. Most importantly, the findings demonstrate that digital literacy partially mediates the relationship between digital transformation and organizational resilience. This suggests that digital transformation strengthens organizational resilience not only through technological and structural mechanisms, but also by enhancing their ability to effectively use and adapt digital technologies.